Engineering external heart assist device - Bašić, Petar Frano (Department of Mechanical Engineering, 2016)
The work described herein is an independent and original work carried out in the Department of Chemical Engineering on a heart assist device which was designed, built and tested in the laboratory. The project can be divided into a mechanical and an electrical task, both of which were undertaken by the author. The electrical task involved design and construction of a portable console adapted to receive a triggering signal and to activate a series of controls either in a sequential or singular fashion. The system also comprises a pulse frequency counter and a safety shut- off control circuits. A portable pressure-vacuum supply system and a pressure pulsating mechanism comprise the work done in completing the mechanical task. Of the two pressure pulsating mechanisms built and tested in the laboratory it is shown that a minimum flow, rigidly enclosed system is superior to a high flow, variable volume one. The design of the electronic console, pressure supply system and pressure pulsating mechanism is described and a description of the laboratory tests carried out so far is given.